Visualisasi Data Sebagai Layanan Perpustakaan dalam Membantu Pertumbuhan Ekonomi - Faizhal Arif Santosa (Pustakaloka, 2022)
Data visualization is a series of data processing processes that produce information in a dynamic visual form. Many libraries around the world have embraced data visualization as a decision-making tool to assist them in making key decisions, but few have discussed the possibilities for libraries to employ this technology to help their users' economic growth. The closeness to life in the library, the opportunities for libraries as services based on social inclusion, as well as the challenges that arise for librarians are discussed in this article. The method used is a literature study of literature sources related to data visualization, business, libraries, and librarian competencies. The result is that the concept of data visualization resembles daily activities in the library, namely repackaging information and making statistics. Data visualization aids librarians in transforming data into actionable information for decision-making and serving it to users. Data visualization opens up opportunities for libraries to be used as services based on social inclusion to help the economic growth of their users. The challenge for librarians is the limited skillsets for this technology. To develop their skills, librarians are urged to enroll in education and training programs.